The role of occupational and physiotherapy in multi-modal approach to tackling delirium in the intensive care. (November 2017) - Rains, Jenny; Chee, Nigel
The presence of delirium within critical care remains a long-standing challenge for patients and clinicians alike. A myriad of pre-disposing and precipitating factors lead to this patient cohort being high risk for developing delirium during their critical care stay. Until now, non-pharmacological management of these patients usually encompasses a 'bundle' of principles to reduce delirium days. These bundles have limited focus on the entire multi-disciplinary team (including occupational therapists and physiotherapists) who could assist with the reduction of delirium. The purpose of this analysis is to review the current literature and develop a mnemonic, which may help facilitate collaborative working for patients with delirium. Electronic databases were searched for non-pharmacological managements of delirium within intensive care settings, after 2006. Critical appraisal using Critical Appraisal Skills Programme methodology was completed by the author. Multi-intervention approaches and bundles are successful at reducing delirium days, and in some cases, reducing hospital length of stay. The key components of these bundles include spontaneous breathing trials, daily sedation holds, addressing pain relief, early mobilisation and to a small extent normalisation of a daily routine. There is limited research into the role of therapy within this patient group, but there is a role for cognitive therapy, functional tasks, and a greater rehab emphasis within other patient populations such as stroke and elderly care. The critical care population have similar rehabilitation needs to these groups, and therefore would benefit from similar treatment plans. Critical care patients with delirium may benefit from a range of additional therapeutic activities to reduce the duration of delirium. The D.E.L.I.R.I.U.M mnemonic has been developed to encompass all the key elements of current delirium research in a simplistic memorable fashion. Further work is needed to trial the usefulness of the mnemonic in clinical practice to enable the entire multi-disciplinary team work collaboratively to reduce delirium with the intensive care.